Effects of a language stimulation program in children with poor school performance from a human settlement of Chorrillos - Dioses Chocano, Alejandro (2000)
The objective of the present study was to determine if a systematic program of stimulation of the language that impacted in the lexicon  semantic aspects, improved the yield in the area of children's integral communication with low school yield that you/they studied the first degree of primary education in a school belonging to a marginal urban area of Metropolitan Lima. Children's of 30 two groups and 22 students were studied each one, the first of them that presented low school yield, participated in the program of stimulation of the language, while the second, conformed by children with yield school average, it served as group control, both groups attended the same school and they were assisted by the same teachers. A test of lexical fluency was used and one of vocabulary, which were administered before lo both groups and after the experience, also, the notes of the area of integral communication were controlled obtained by the children in the exams surrendered in the c1assroom. The obtained results showed that a significant increment exists in the vocabulary and the lexical fluency of the students that participated of the program, with that which is demonstrated that the outlined curricular design is valid to improve these aspects of the language: however; this achievements, were not reflected in significant increments in the punctuations reached during the classroom exams corresponding to the area of integral Communication.